Monitoring the Effect of Variegated Forest Soil Amendments on the Germination and Early Growth of Irvingia gabonensis (O Rorke, Baill) - Egwunatum, A. E.; Dolor, D. E.; Ofobike, C. J. (Cutting-edge Research in Agricultural Sciences Vol. 6, 2021)
This study evaluated the early germination and growth variables of Irvingia gabonensis under organically primed and thermally amended soil media. Six media were prepared from Gmelina plantation topsoil by amendment with poultry waste (T2), river sand (T3) and combusted forest floor litters for 5 (T4), 10 (T5), 15 (T6) and 20 (T7) minutes respectively to contrast a control topsoil (T1). Soil media were analyzed for critical nutrient properties and engaged in the germination and early growth trial of Irvingia replicated three times and arranged in a completely randomized design. Data collected were analyzed with ANOVA and significant means separated with the Duncan multiple range test. The results showed that Ca/Mg ratio was widest for T3, least CEC (13.2 meq/100 g soil) by T7 and slightly acidic pH (H2O) for T1 and T2 while T3, T4, T6 and T7 were alkaline. Germination at 6 WAS was T4 (100%)> T1=T2=T5 (85.71%) > T3 (71.43%) > T6 (42.86%) > T7 (0%). The growth variables of seedling varied significantly (P<0.05) with T3 and T4 comparing favorably in collar diameter (4.50x10-1± 0.05 mm) and leaf area (35.08±4.85 mm2) although T3 recorded the highest stem height (117.79±0.42 mm). The study recommends the use of least thermally modified media (T4) and primed topsoil-river-sand (T3) in favour of the conventional topsoil (T1), for fast germination in view of conserving food reserve for the critical early growth period of I. gabonensis in pursuit of its domestication in nutrient degraded soils. Therefore the domestication of this near threatened and economic forest tree species is possible with a combination of these cheap and readily available amendments at the nursery and plantation establishment phases.